Feasibility Analysis of Cassava Farming Income in Mojo Village, Cluwak Sub-District Pati District Central Java - Tresnanto, Yohanes Wisnu; Nuswantara, Bayu (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
The research objective was to obtain an overview of farming costs and revenue and analyze the feasibility of cassava farming income in Mojo Village. The research was conducted from March 2019 to April 2019. The type of research was descriptive quantitative. The sampling technique used is a simple random sampling technique to determine the number of samples using the Slovin formula with an error rate of 10% with a sample of 53 farmers as respondents. Data analysis techniques include cost analysis, revenue analysis, and business feasibility analysis R/C Ratio and Break-Even Point. Data types use primary and secondary data with data collection techniques using interviews, observation, questionnaires, and literature study. The results showed that the total cost was IDR10.836.545, revenue was IDR39.865.508, and income was IDR29.028.963 per hectare in 1 planting season. The feasibility of cassava farming is based on the Revenue Cost Ratio (R/C) of 3.68, which means that cassava farming is feasible to be implemented. The Break-Even Point shows that the production BEP is 8.014 kg, the price BEP is IDR383. In comparison, the average production of cassava farming in Mojo Village is 28.424 kg, with an average price per kg of IDR1.403, more significant than the calculated value. BEP for production and BEP for a price indicate that cassava farming is feasible to be implemented.